Ionization of uracil in collisions with highly charged carbon and oxygen ions of energy 100 keV to 78 MeV - Agnihotri, A. N. (2012)
Fast highly charged C and O ion-induced total ionization of an RNA base molecule, uracil (C4 H4 N2 O2 , m = 112 amu), has been Investigated in a wide energy range of keV to MeV. A combined study of the collision products using a time-of-flight mass spectrometer and an electron spectrometer allows one to determine absolute total ionization cross sections (TCSs). Experimental measurements of TCSs are compared to theoretical predictions performed in the classical trajectory Monte Carlo and classical over-barrier (CTMC-COB) andquantum mechanical (Continuum Distorted Wave with Eikonal Initial State and first-order Born with correct boundary condition) frameworks. The overall energy dependence of the TCSs is approximately reproduced by the models, especially well in the high energy range. The CTMC-COB model provides an excellent agreement for the high-energy data. The projectile charge-state q dependence of TCSs deviates from the well-known quadratic behavior in ion-atom collisions.